2018
DOI: 10.7553/84-2-1762
|View full text |Cite
|
Sign up to set email alerts
|

Navigating the rising metrics tide in the 21st century: which way for academic librarians in support of researchers in sub-Saharan Africa?

Abstract: Academic librarians in sub-Saharan Africa, just like their counterparts in the rest of the world, are under pressure to provide relevant information services to satisfy varied client needs. Research administrators, grant offices, researchers, students and university managers, among others, are increasingly turning to academic librarians for information to meet their myriad research-related information and metrics needs. Sub-Saharan African countries' emphasis on strengthening science, technology and innovation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 19 publications
0
25
0
1
Order By: Relevance
“…The South African government places a strong emphasis on research and this is demonstrated by the amount of financial support which is channelled to universities and other research institutions (Onyancha 2018). A recent testimony of the South African government's respect for research is the appointment of a ministerial advisory committee on COVID-19.…”
Section: The South African Academic Research Environmentmentioning
confidence: 99%
See 3 more Smart Citations
“…The South African government places a strong emphasis on research and this is demonstrated by the amount of financial support which is channelled to universities and other research institutions (Onyancha 2018). A recent testimony of the South African government's respect for research is the appointment of a ministerial advisory committee on COVID-19.…”
Section: The South African Academic Research Environmentmentioning
confidence: 99%
“…In order to understand the shifts and changes in the research landscape in general, and in particular the role of the librarian, this chapter is informed by the research life cycle framework. This framework has been successfully applied in part or in full by researchers focussing on new roles of librarians in research such as Chiware (2020), Onyancha (2018), and Chung, Kwon, and Lee (2016). Although the research life cycle may slightly differ from one discipline to the other, there is a general consensus on key principle stages, namely idea generation or discovery, research proposal, conduct research, publish research, or results dissemination.…”
Section: The Growing Role Of the Librarian In The Research Life Cycle...mentioning
confidence: 99%
See 2 more Smart Citations
“…The transformed roles, innovative services and future of academic libraries have been the focus of attention by many researchers around the world (Catalano et al , 2018; Cox et al , 2019; Dempsey and Malpas, 2018; Feret, 2018; Schulte et al , 2018; Sewell and Kingsley, 2017) and in South Africa (Chiware and Becker, 2018b; Hodonu-Wusu and Lazarus, 2018; Kwanya and Stilwell, 2018; Moll and Moll-Willard, 2019; Ocholla et al , 2016; Ocholla and Ocholla, 2017; Onyancha, 2018; Raju et al , 2018; Wilson et al , 2019). The result has been the creation of new library spaces and services, which are suitable for the needs and orientation of individual institutions (Dempsey and Malpas, 2018); (Ocholla et al , 2016), in response to the rapidly changing landscape of higher education, influenced by a strong research, teaching and learning agenda; ICTs; university ranking; community engagement (for contextualizing research and teaching) and the 4IR, all of which demand that library services be accessible anytime, and anywhere.…”
Section: Case Study – Academic Library Responsementioning
confidence: 99%